2019
DOI: 10.18632/oncotarget.26838
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-203 impacts on the growth, aggressiveness and prognosis of hepatocellular carcinoma by targeting MAT2A and MAT2B genes

Abstract: Hepatocellular carcinoma (HCC) is characterized by the down-regulation of the liver-specific methyladenosyltransferase 1A ( MAT1A ) gene, encoding the S-adenosylmethionine synthesizing isozymes MATI/III, and the up-regulation of the widely expressed methyladenosyltransferase 2A ( MAT2A ), encoding MATII isozyme, and methyladenosyltransferase 2B ( MAT2B ), encoding a β-subunit without catalytic action that regulates MATII enzymatic activity. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Recent research indeed showed that miR-21-3p lessens MAT2A and MAT2B expression in HepG2 cells by targeting their 3’-primer untraslated regions (3′-UTRs); it also inhibits cell growth [169]. Furthermore, we found that miR-203 expression is inversely correlated with MAT2A and MAT2B expression and the expression of HCC proliferation and aggressiveness markers [168]. MiR-203 expression is genetically regulated and contributes to determining patients’ outcomes [168].…”
Section: Possible Effects Of the Manipulation Of The Mat1a:mat2a Smentioning
confidence: 83%
See 2 more Smart Citations
“…Recent research indeed showed that miR-21-3p lessens MAT2A and MAT2B expression in HepG2 cells by targeting their 3’-primer untraslated regions (3′-UTRs); it also inhibits cell growth [169]. Furthermore, we found that miR-203 expression is inversely correlated with MAT2A and MAT2B expression and the expression of HCC proliferation and aggressiveness markers [168]. MiR-203 expression is genetically regulated and contributes to determining patients’ outcomes [168].…”
Section: Possible Effects Of the Manipulation Of The Mat1a:mat2a Smentioning
confidence: 83%
“…Additionally, MAT2A cross-talks with polyamine synthesis in colon and liver carcinoma [166], and the sumoylated Matα2 protein protects human colon and liver cancer cells from apoptosis by regulating BCL2 expression [167]. Furthermore, we recently demonstrated an oncogenic activity of both MAT2A and MAT2B genes [168]. These finding suggest that these genes could be targets of anticancer therapies.…”
Section: Possible Effects Of the Manipulation Of The Mat1a:mat2a Smentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we for the first time illustrated miR-203 as another anti-tumour executor of luteolin. miR-203 has been widely identified as an anti-tumour miRNA [17][18][19][20], but its exact function in breast cancer is confusing. Two of the previous studies reported miR-203 as an oncogene, as silence of its expression inhibited breast cancer cells colony formation, transformation, stemness and migration [21,37].…”
Section: Discussionmentioning
confidence: 99%
“…miR-203 is one of such oncogenic miRNA that locates at chromosome 14q32.33. The antitumour role of miR-203 has been found in various kinds of cancers, such as colorectal cancer [17], hepatocellular carcinoma [18], gastric cancer [19], prostate cancer [20] and so forth. However, miR-203 exerted contradictory roles in breast cancer.…”
Section: Introductionmentioning
confidence: 99%